2013
DOI: 10.1515/aot-2012-0079
|View full text |Cite
|
Sign up to set email alerts
|

The importance of induced aberrations in the correction of secondary color

Abstract: Much publicity has been given to the art and science of choosing glass types for the reduction of secondary color, particularly for systems (such as achromats) in which all the elements are in contact. Although it has long been recognized that airspaces between elements can influence chromatic aberration and can even be used to reduce or correct secondary color, comparatively, little emphasis has been placed on this in the published literature. This tutorial is intended to call attention to the induced compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…So, the LCA of a lens can be considered as some kind of combination of the intrinsic and induced chromatic aberrations, a detailed discussion can be found in the Ref. 57.…”
Section: Paraxial Lcamentioning
confidence: 99%
“…So, the LCA of a lens can be considered as some kind of combination of the intrinsic and induced chromatic aberrations, a detailed discussion can be found in the Ref. 57.…”
Section: Paraxial Lcamentioning
confidence: 99%
“…Over the years, a number of papers with analytical methods for finding optimal glass combinations for color correction have been published [1][2][3]. In recent years much attention in this field has also been paid to the role of induced aberrations [4][5][6]. It was shown that for complex optical systems the highest degree of optical correction is achieved when both intrinsic and induced terms of color aberrations are considered [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in the past that induced aberrations can have a significant impact on the correction of secondary axial color [4,5]. Today, the importance of induced aberrations for the correction of secondary axial color is again under investigation [6][7][8]. Actually, there are certain types of optical systems that exclusively take advantage of induced effects to obtain a chromatically corrected image [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, to determine the latter one, a second paraxial ray needs to be traced. In present research, analytical expressions for induced color aberrations are obtained only for selected examples and certain special cases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%